OVERCOME THE PROBLEM OF DEVIANT BEHAVIOR THROUGH GROUP GUIDANCE TECHNIQUES FOR JUNIOR HIGH SCHOOL STUDENTS - Syahnur Rahman (Universitas Muhammadiyah Purwokerto, 2021)
ABSTRAK: The main problem in this research is to overcome the low ability of students to solve problems., Which almost every day many problems that arise such as: personal, social, career and even learning difficulties. The sample in this study, namely 7th grade SMP 12 Malang.The results of the assessment appear in table 4.3 which states